2022
DOI: 10.15328/cb1272
|View full text |Cite
|
Sign up to set email alerts
|

In silico drug-likeness, biological activity and toxicity prediction of new 3,5-bis(hydroxymethyl)tetrahydro-4H-pyran-4-one derivatives

Abstract: This paper presents the results of predicting drug-likeness, biological activity, and toxicity for 8 new derivatives of 3,5-bis(hydroxymethyl)tetrahydro-4H-pyran-4-one using bioinformatic methods. The physicochemical and pharmacokinetic parameters of the studied compounds were determined, in silico screening for biological activity and prediction of their toxicity were carried out. Physicochemical and pharmacokinetic parameters were evaluated using the Molinspiration Cheminformatics service. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to Table 3 , the selected phytocompounds may act as both CYP3A4 inhibitors and substrates. This enzyme is responsible for the majority of medicinal metabolism in the human organism system [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 3 , the selected phytocompounds may act as both CYP3A4 inhibitors and substrates. This enzyme is responsible for the majority of medicinal metabolism in the human organism system [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3. Pharmacokinetic properties and toxicity analysis of the selected drug molecules computed using the pkCSM web-tool [55,87]. According to the excretion profile, these phytocompounds can be excreted from the bloodstream in a relatively effective manner with virtually no risk of drug formation in the organism because the results of the study demonstrated that these phytochemicals had a total clearance (TC) value of 0.5 (log mL min −1 kg −1 ), with the only exception being astilbin, which had a negative value of −0.28.…”
Section: Drug-likeness Profile (Admet)mentioning
confidence: 99%
“…The compounds physicochemical predictions are used to assess the similarity of the tested compounds to drugs based on the Lipinski's rule of five (Ro5).The Lipinski's Ro5 is an in silico tool for evaluating physicochemical properties, which is critical in determining drug safety prior to marketing as an identification process during pre-clinical trials. Other studies have found that, in addition to the Lipinski's Ro5 parameter, the descriptor of a test compounds physicochemical properties is topological polar surface area (TPSA) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical prediction based on The Lipinski's rule of five (Ro5) consisting of molecular weight (BM), number of hydrogen bond donor (HBD), number of hydrogen bond acceptor (HBA), oil to water partition coefficient (Log P) and number of bonds that can be rotated (Torsion) [15]. Other studies have added another descriptor of physicochemical properties, namely the topological polar surface area (TPSA) [16]. Toxicity prediction in this study used 2 programs that can be accessed online, namely ProTox-II and pkCSM.…”
Section: Prediction Of Physicochemical Properties and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation